2003
DOI: 10.1016/s0929-1393(03)00043-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disturbance and ecosystem on decomposition

Abstract: Decomposition of organic matter integrates collective activities of organisms within the soil food web. We compared decomposition of museum board (predominantly cellulose) and balsa wood substrates in 18 sites chosen to represent a completely nested design with two disturbance levels nested within three ecosystems (agriculture, wetland, and forest) and ecosystems nested within three land resource regions (LRR) in North Carolina. Percentage mass remaining and daily rate of mass loss of museum board and balsa wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 43 publications
0
26
1
Order By: Relevance
“…Decomposition reflects changes in microbial and invertebrate populations and communities. Generally, decomposition rate at the study site (cellulose 0.24-0.69% loss/day; lignin/cellulose mixture 0.19-0.62% loss/day) were slower than in other studies measured either with litter baskets (Neher et al, 2002) or litter bags in other temperate deciduous forest soils. For example, cellulose degraded 36.3% and lignin 8.1% within 12 weeks (Entry and Backman, 1995) compared to 31.0 and 41.7% total mass loss of cellulose and lignin/cellulose (initially 22% lignin, 76% cellulose), respectively, during our study of 15 weeks.…”
Section: Decompositioncontrasting
confidence: 72%
“…Decomposition reflects changes in microbial and invertebrate populations and communities. Generally, decomposition rate at the study site (cellulose 0.24-0.69% loss/day; lignin/cellulose mixture 0.19-0.62% loss/day) were slower than in other studies measured either with litter baskets (Neher et al, 2002) or litter bags in other temperate deciduous forest soils. For example, cellulose degraded 36.3% and lignin 8.1% within 12 weeks (Entry and Backman, 1995) compared to 31.0 and 41.7% total mass loss of cellulose and lignin/cellulose (initially 22% lignin, 76% cellulose), respectively, during our study of 15 weeks.…”
Section: Decompositioncontrasting
confidence: 72%
“…Using cellulose strips in humus layers, Kurka et al (2001) found cation exchange capacity to positively correlate with decomposition. Neher et al (2003) also found there was a trend for the percentage of soil organic matter to positively correlate with decomposition. High organic matter often correlates with high cation exchange capacity as organic matter colloids have large quantities of negative charges.…”
Section: Environmental Variables and Decompositionmentioning
confidence: 73%
“…This is in agreement with the correlations that were observed between residue quality and microbiological characteristics (discussed in the preceding paragraph). Decomposition is a useful indicator of soil condition because it integrates the collective activities of soil organisms involved in the soil food web (Neher et al 2003). Therefore, soil microorganisms play key roles in sustaining the fertility and productivity of agricultural soils.…”
Section: Discussionmentioning
confidence: 99%